Anticonvulsant effect of sodium cyclamate and propylparaben on pentylenetetrazol‐induced seizures in zebrafish. Issue 4 (13th February 2017) - Pisera‐Fuster, Antonella; Otero, Sofía; Talevi, Alan; Bruno‐Blanch, Luis; Bernabeu, Ramón
Abstract: Screening for novel anticonvulsant drugs requires appropriate animal seizure models. Zebrafish provide small, accessible, and cost‐efficient preclinical models applicable to high‐throughput small molecule screening. Based on previous results in rodents, we have here examined the effects of artificial sweetener sodium cyclamate and antimicrobial agent sodium propylparaben on a model of pentylenetetrazole (PTZ)‐induced seizures in zebrafish. Sodium cyclamate reduced the bursts of hyperactivity, the spasms, increased the latency to spasms, and the latency to seizure, while propylparaben increased the latency to spasms. The results show the potential of zebrafish to detect novel anticonvulsant compounds while they also demonstrate the ability of two commonly ingested chemical compounds to modify the seizure threshold when were administrated at low concentration. Abstract : PTZ induced seizures in zebrafish, suggesting that can be used as a preclinical animal model to study seizure. Using this model, we demonstrate that sodium cyclamate (an artificial sweetener) and propylparaben (antimicrobial agent) modify the seizure threshold. In red: computer‐generated behavioral traces produced by pentylenetetrazole (PTZ), valproate (VPA), sodium cyclamate (SC), and propylparaben (PP) exposure in adult zebrafish tested in a 15 min observation tank.